Performance analysis of HCCI and PCCI engines using computational fluid dynamics. (26th March 2021) - Upadhyay, Pushpendra; Rana, K.B.; Tripathi, B.
In the current study, a numerical simulation for a three dimensional model of internal combustion (IC) engine consists of inlet valve, exhaust valve, inlet manifold and exhaust manifold, was carried out to analyse the HCCI and PCCI strategies using ANSYS 16.2. The computational fluid dynamics (CFD) analysis was carried out for different swirl numbers and essentially moderate values of the engine speed. The converged results of both the combustion strategies were compared for different wall adjacent temperature, mass average static pressure, apparent heat release rate and mass average turbulent kinetic energy. The outcome of simulations reflected that a PCCI combustion strategy is better than HCCI combustion strategy at lower rpm, while at the moderate and higher values of engine rpm, HCCI combustion strategy demonstrated better performance in terms of temperature, pressure and turbulent kinetic energy. Interestingly, the exergy destruction rate was observed higher in the case of homogeneous charge compression ignition combustion strategy.